Quantifying Hyperbole: Explicit Estimates of Exaggerated Utterances - Бріттані Харман; Хеннессі Страйн (Психолінгвістика)
Purpose. People are exposed to exaggeration in some form every day. They must comprehend and interpret the hyperbole, or conversational overstatement, to which they are exposed. Research suggests that people cognitively correct hyperbolic utterances using information retrieved from memory to generate estimates of what really occurred in the situation or event and the sampling of memory traces during the interpretation of utterances is influenced by the form and contextual elements of the utterance.